The elite judo female athlete’s heart - Milovančev, Aleksandra; Petrović, Milovan; Miljković, Tatjana; Ilić, Aleksandra; Mudrinić, Tatjana Redžek; Miljković, Aleksandar; Ivanov, Olivera; Tripunović, Jelena; Anđelic, Bogdan; Bianco, Antonino; Drid, Patrik (Frontiers in Physiology, 2022)
Purpose: There is a paucity of data on physiological heart adaptation in elite-level judo female athletes. This study aimed to assess left ventricular morphology and function in highly trained elite female judokas. Methods: The study prospectively included 18 females aged 23.5 ± 2.25 years, nine elite level judokas, and nine healthy non-athlete volunteers. All participants underwent a medical examination, electrocardiogram, and transthoracic 2D echocardiogram. Left ventricular diastolic and systolic diameters and volumes were determined, and parameters of left heart geometry and function (systolic and diastolic) were measured, calculated, and compared between groups. Results: When groups were compared, judokas had significantly increased left ventricular cavity dimensions p < 0.01, left ventricular wall thickness p < 0.01, and volumes p < 0.01. Elite female judokas exhibited left ventricular dilatation demonstrated as high prevalence increased end-diastolic volume/index, and increased end-systolic volume/index in 88.9% of judokas vs. 0% in controls, p < 0.01. Left ventricle mass/index was significantly increased in judokas, p < 0.01), with a 43.3% difference between groups. The majority (77.7%) of judokas had normal left ventricular geometry, although eccentric hypertrophy was revealed in 2 (22.2%) of judokas. Conclusion: Elite, highly trained female judokas exhibit significant changes in left heart morphology as a result of vigorous training compared to non-athletes. These findings suggest that female judokas athletes’ heart follows a pattern toward chamber dilatation rather than left ventricular wall hypertrophy.